Graphene oxide-based polymer nanocomposites for the enhanced removal of lead (II) from water - Medina, Ruji P. (College of Engineering, University of the Philippines Diliman, 2014)
Lead in the aquatic environment is a major global concern owing to its toxic nature. In this study, novel graphene oxide-chitosan-poly(acrylic acid) (GO-CS-PAA) polymer nanocomposite hydrogel beads produced via a simple and direct method were used as adsorbents to remove lead from water. Optimization studies employing the Box-Behnken Design (BBD) in response surface methodology (RSM) was able to determine the base polymer composition with highest lead removal capability. Enhancement of lead removal was accomplished by the infusion of graphene oxide nanomaterial. Investigation into the polymer structure by crosslinking with glutaraldehyde (GLA) pointed to the formation of a semi-interpenetrating polymer network (semi-IPN). ATR-IR spectroscopy confirmed the successful integration of CS and PAA and the interaction of GO with the polymers which was mainly physical. Scanning electron microscopy revealed that dry hydrogel beads had convoluted surface morphology and homogeneous, impermeable internal structure. To maximize adsorptive capacity, wet beads were tested to utilize the intraparticle diffusion mechanism. Adsorption assays showed that amount of GO blend had a positive effect on metal uptake due to addition of oxygen-containing functional groups. Protonation of functional groups at low pH values severely impaired metal uptake and best adsorption was observed at pH 5. The adsorption kinetics was best described by the pseudo second-order model indicating that chemisorption was rate-determining. Fitting to the intraparticle diffusion model suggested that adsorption occurred in three distinct phases. Adsorption isotherms showed excellent fit to the Langmuir isotherm and CS-PAA beads with 5% GO content had the highest Pb2+ adsorption capacity of 138.89 mg/g. When this material was subjected to three adsorption-desorption cycles, high values were obtained signifying good reusability. Reusability and the enhanced lead removal capability demonstrated that the newly-developed GO-CS-PAA hydrogel beads are excellent adsorbent materials for the removal of lead from aquatic environment.